A NUMERICAL SIMULATION OF MORPHOLOGICAL PROCESSES FOR A NAVIGATION CHANNEL - Diep, Nguyen Van; Chung, Dang Huu (Vietnam Journal of Mechanics, 2007)
The finite difference method was applied to simulate the morphological processes for a. navigation channel Mathematical equations were based on the SUTRENCH and PROFILE models proposed by L. C. van Rijn. The difficulties of treatment for bed boundary conditions were overcame flexibly by using the interpolation functions with high accuracy. The results obtained showed that the simulation is very suitable and able to be applied to practice problems.